Correction: Effect of temperature and moisture contents on dielectric properties at 2.45 GHz of fruit and vegetable processing by-products. Issue 32 (19th May 2020) - Solyom, Katalin; López, Pilar Rosales; Esquivel, Patricia; Vásquez-Caicedo, Ana Lucía
Abstract : Correction for 'Effect of temperature and moisture contents on dielectric properties at 2.45 GHz of fruit and vegetable processing by-products' by Katalin Solyom et al., RSC Adv., 2020, 10, 16783–16790, DOI: ; 10.1039/C9RA10639A .